STUDI PERBANDINGAN ANALISIS VITAMIN E MINYAK SAWIT MERAH TERSAPONIFIKASI ANTARA METODE SPEKTROFOTOMETRI UV-VIS DAN KCKT - Arlina Mayharty Andulaai; Ruslan Ruslan; Hardi Ys.; Dwi Juli Puspitasari (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2017)
A research about a comparative study of spectrophotometry UV-Vis and HPLC method for the analysis of vitamin E in saponified red palm oil has been done. This research aims to compare the results of analysis using Spectrophotometer UV - Vis and HPLC to determine the concentration of vitamin E in red palm oil previously saponified and extracted. HPLC analysis was carried out using an RP-18 column and mobile phase composed a methanol and water ( 86:14 ), with a flow rate of 1 ml/min and UV detection at 290 nm. For the Spectrophotometric UV-Vis analysis, hexane was used as a solvent and the wavelength at 298,5 nm was selected for the detection. The results are the concentration of vitamin E using spectrophotometric and HPLC method was respectively 104.5 ppm and 127 ppm.Keyword: Vitamin E, Red Palm Oil, saponification, extraction, spectrophotometry Ultra Violet -Visible, High Performance Liquid Chromatography